Tau Inclusions in Alzheimer's, Chronic Traumatic Encephalopathy and Pick's Disease. A Speculation on How Differences in Backbone Polarization Underlie Divergent Pathways of Tau Aggregation - Cieplak, Andrzej Stanisław (Frontiers in Neuroscience, 2019)
Tau-related dementias appear to involve specific to each disease aggregation pathways and morphologies of filamentous tau assemblies. Here we elucidate molecular mechanism of tau aggregation based on the PMO theory of protein secondary and tertiary structure (Cieplak, A. S. (2017). PLoS ONE 12: e0180905) and the recent structural evidence, aiming to account for the reported differences in fibril-core structure, cross-seeding of isoforms, response to non-reducing conditions, and homologs’ aggregation properties. The proposed model suggests that in contrast to Alzheimer’s disease, the assembly of tau prions in Pick’s disease would be facilitated by a moderate drop in pH that accompanies e.g. transit in the endosomal system, neuroinflammation or ischemic injury.